Nirmal Sengupta. Managing Common Property. Irrigation in India and the Philippines. Nueva Delhi/Newbury Park/ Londres: Sage, 1991, 283 pp. (Indo-dutch studies on develpment alternatives-6) (cuadros, diagramas y mapas). - Susana B. C. Devalle (El Colegio de México, A.C., 1992)
-